3 - De la dépendance alimentaire à la dépendance financière, l’engrenage... - Najib AKESBI (Africa Development, 1985)
Food dependency in Morocco is first and foremost due to an export-oriented agricultural model of development which was strongly advised by the World Bank and the IM.F. The Moroccan case is mther special with reference to the issue of the role of agriculture in the develop ment process and to the general trend observed in the past twenty five years in most developing countries. To be sure, as of the mid-sixties, the Moroccan leaders gave top priority to agriculture, contrary to many coun tries especially African countries which favoured industry in their develop ment plans over agriculture. Thus the latter was supposed to feed the population, create jobs, improve revenues, provide foreign exchange, yield a surplus which could be channeled toward funding other economic sectors. Over-all, massive measures were taken to serve the planned model. They included public investments, a code of investments, subsidies, taxes, pricing policy, organization of markets, agricultural credit... Important, multi farious means were used to this end. Yet, after over two decades of building such an export-oriented agricultural model, results appear disappointing, to say the least. The whole agricultural output is on the decline, the trade balance with reference to food is deeply in the red, food dependency has dangerously soared, the gap in social and spatial inequalities has more than ever widened... In short it is obvious that the model has failed. Worse still not only did the financial model built to back up the export-oriented agricultural model lack the means to extract surplus in the very areas which could best generate it but moreover it increased its «pres sure» excessively on a specific part of the tax base, i.e., consumption and salaries. Yet these are precisely the choice « targets» of tax systems, which are being thrashed by the crisis. The potentials of such a system are highly limited by reduced consumption as well as the freeze on salaries and the only temporary outlet of this system is to resort to external loans which become the only condition for the country to survive financially. Thus the food dependency is coupled with a financial dependence. Both feed on each other and the resulting complication of circumstances drives the country into a deeper and deeper decline.